Anterior lateral thigh osteomyocutaneous free flap reconstruction in the head and neck: The anterolateral thigh osteomyocutaneous femur bone flap. Issue 12 (16th June 2016) - Brody, Robert M.; Pandey, Nirnimesh C.; Bur, Andrés M.; O'Malley, Bert W.; Rassekh, Christopher H.; Weinstein, Gregory S.; Chalian, Ara A.; Newman, Jason G.; Cannady, Steven B.
ABSTRACT: Background: The anterolateral thigh (ALT) free flap is one of the most commonly used donor sites in head and neck reconstruction, however, it is not typically considered when an osseous component is needed. Methods: Soft tissue harvests, cadaveric study, and retrospective analysis of a series of 10 patients undergoing angiography were performed to assess vascular supply to the femoral cortex. In 6 patients, corticocancellous split‐femur was incorporated into the ALT to reconstruct bony defects of the head and neck. Results: There is a consistent blood supply to the femur from the lateral femoral circumflex artery both intraoperatively and on angiography. No fractures or orthopedic injuries have been seen to date. None of the patients had complications of bone harvest, such as deep vein thrombosis or pulmonary embolism. Conclusion: The ALT osteomyocutaneous (ALTO) flap has consistent vascular anatomy to the femoral cortex. This flap provides additional corticocancellous bone and overlying vastus intermedius muscle for the reconstruction of complex craniofacial defects. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1788–1793, 2016